ANALISIS SUPPLY CHAIN MANAGEMENT PADA COFFEE SHOP SUKABUMI - Pratiwi Suryanti, Rintan; Widda Inka, Ulfa; Ratu Fortuna Pattinasarani, Jasmine; Sintya Juliani, Dinda; Rafli Pratama, Muhammad; Aziz Husyairi, Khoirul; Selma Agnia Elfath, Amadea; Rahma Azzahra, Maulania (Jurnal Cakrawala Ilmiah, 2025)
The purpose of this study is to analyze the supply chain at Coffee Shop Ordinary in Sukabumi and identify waste in the business process. The method used is a qualitative approach with Value Stream Mapping (VSM) as the main analytical tool. The object of the study is Coffee Shop Ordinary, a business that has been operating for 29 years and serves students in Sukabumi. Data were collected through semi-structured. Observations, operational document analysis, and semi-structured interviews. The results of the value stream mapping indicate that the total lead time is approximately 45 minutes per order, consisting of 5 minutes of waiting time, 20 minutes of added activities (VA), such as preparing and serving coffee, and 20 minutes of non-added activities (NVA), which include order queues and equipment setup. Process Cycle Efficiency (PCE) was calculated at 44%, which indicates that Coffee Shop Ordinary's supply chain management is still below the ideal target of approximately 60% for a cafe business, so there is an opportunity for lean improvement